Hypermethylation of two CpG sites upstream of CASP8AP2 promoter influences gene expression and treatment outcome in childhood acute lymphoblastic leukemia - Li, Zhi-Gang; Jiao, Ying; Li, Wei-Jing; Deng, Guo-Ren; Cui, Lei; Gao, Chao; Zhao, Xiao-Xi; Wu, Min-Yuan; Jia, Hong-Ti (Leukemia research, 2013)
DNA hypermethylation of Caspase 8 associated protein 2 (CASP8AP2) and its role in childhood acute lymphoblastic leukemia (ALL) is unclear. We analyzed methylation status of CpG sites upstream of CASP8AP2 gene in 86 children with ALL by bisulfite sequencing and quantitative PCR. Methylation percentage of two CpG sites at positions of −1189 and −1176 was inversely correlated with mRNA expression (Spearman correlation: −0.333, P=0.002). High methylation was associated with the existence of minimal residual disease (MRD) at day 78 (P=0.035), The patients in high methylation group had a poor treatment outcome. The combination of methylation level and MRD at day 33 might improve current risk stratification.